Role of intestinal microbiota in transplantation outcomes. Issue 2 (June 2015) - Taur, Ying; Jenq, Robert R.; Ubeda, Carles; van den Brink, Marcel; Pamer, Eric G.
Abstract: While allogeneic hematopoietic stem cell transplantations have a curative potential, infections and graft-versus-host disease remain significant problems. The intestinal microbiota can influence responses to cancer chemotherapy and the role of the microbiota in affecting allogeneic hematopoietic stem cell transplantation outcomes is increasingly appreciated. The following paper discusses the most recent developments in this area.